POLA PERTUMBUHAN POPULASI VORTICELLA GLOBOSA PADA MEDIA KULTUR AIR RENDAMAN ALANG-ALANG, BEKATUL DAN GEDEBOK PISANG DENGAN BERBAGAI KONSENTRASI - Nugroho, Trias; Budijastuti, Widowati; Faizah, Ulfi (LenteraBio: Berkala Ilmiah Biologi, 2013)
Vorticella included in Protozoa that have an important role mainly on aquatic life, such as bioindicators, and heavy metal bioremediation agents on heavy metals contaminated waters with passive and active uptake process, therefore, necessary culture Vorticella enough to be used as bioremediator. This study aimed to describe the growth pattern of Vorticella globosa populations. This study used a completely randomized design with two treatment factors are the type of soaking culture medium of cogon grass, rice bran and banana pseudostem and concentration of 1%, 2% and 3% w/v and EL medium as well as control medium with 3 replications. The parameters measured were the Vorticella globosa population growth curve for 8 days. Vorticella globosa population growth curves were analyzed descriptively. The results showed Vorticella globosa population growth curves have the same pattern, there is a lag, log, stationary, and death phase, but the time for each phase varies.